Framing of same-sex marriage over 17 years in two newspapers is linked to ideology especially in election years. (June 2018) - Lasorsa, Dominic L.; Suk, Jiyoun; Fadnis, Deepa
Over 17 years, the New York Post and New York Times framed same-sex marriage primarily in terms of equality or morality. In 1998-2003, morality framing was more prevalent, especially in the Post. In 2004-2009, morality framing declined in the Post and increased in the Times. In 2010-2014, equality framing increased in both papers. Morality framing increased in election years. Generally, the Post morality framed more than the Times, especially on its opinion pages, and especially during elections.